An Objective Approach for Burkholderia pseudomallei Strain Selection as Challenge Material for Medical Countermeasures Efficacy Testing - Van Zandt, Kristopher E.; Tuanyok, Apichai; Keim, Paul; Warren, Richard L.; Gelhaus, H. Carl (Frontiers in Cellular and Infection Microbiology, 2012)
Burkholderia pseudomallei is the causative agent of melioidosis, a rare disease of biodefense concern with high mortality and extreme difficulty in treatment. No human vaccines are available that protect against B. pseudomallei infection, and with the current limitations of antibiotic treatment, the development of new preventative and therapeutic interventions is crucial. Although clinical trials could be used to test the efficacy of new medical countermeasures (MCMs), the high mortality rates associated with melioidosis raises significant ethical issues concerning treating individuals with new compounds with unknown efficacies. The US Food and Drug Administration (FDA) has formulated a set of guidelines for the licensure of new MCMs to treat diseases in which it would be unethical to test the efficacy of these drugs in humans. The FDA “Animal Rule” 21 CFR 314 calls for consistent, well-characterized B. pseudomallei strains to be used as challenge material in animal models. In order to facilitate the efficacy testing of new MCMs for melioidosis using animal models, we intend to develop a well-characterized panel of strains for use. This panel will comprise of strains that were isolated from human cases, have a low passage history, are virulent in animal models, and are well-characterized phenotypically and genotypically. We have reviewed published and unpublished data on various B. pseudomallei strains to establish an objective method for selecting the strains to be included in the panel of B. pseudomallei strains with attention to five categories: animal infection models, genetic characterization, clinical and passage history, and availability of the strain to the research community. We identified 109 strains with data in at least one of the five categories, scored each strain based on the gathered data and identified six strains as candidate for a B. pseudomallei strain panel.